Multifunctional joint lubricating material as well as preparation method and application thereof
By developing a covalent organic framework material loading poly(ethylene glycol)-poly(N-isopropylacrylamide) microgel layer, combined with multifunctional joint lubricating material loading manganese dioxide quantum dots and anti-inflammatory active ingredients, the problem of fast degradation of joint lubricants and difficult to effectively treat joint inflammation is solved, and the effect of improving joint lubricating and extending joint life is achieved.
Patent Information
- Application Number
- CN202411809634.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-07
AI Technical Summary
Nowadays, articular lubricants degrade rapidly in the body and require frequent injection and supplementation, which increases the risk of bacterial infection and patient pain, and is difficult to effectively treat arthritis.
A multifunctional joint lubricating material is developed, including a covalent organic frame material (COF) and a poly(ethylene glycol)-poly(N-isopropylacrylamide) microgel layer loaded on the COF surface. The poly(ethylene glycol) and poly(N-isopropylacrylamide) in the microgel layer are connected by C-O covalent bonds. The material can also be loaded with manganese dioxide quantum dots and anti-inflammatory active ingredients.
This material can improve the solubility of COF in aqueous solution, improve anti-wear and friction reduction performance, reduce joint wear, prolong joint life, and assist in improving the effect of inflammation treatment by loading anti-inflammatory active ingredients and photothermal conversion performance.
Smart Images

Figure CN119564944A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biomaterials, and more specifically, to a multifunctional joint lubricating material and a preparation method and application thereof. Background Art
[0002] Arthritis is a common chronic disease, known as the "number one disabling disease", affecting the joint health of about 300 million people worldwide. Studies have confirmed that cartilage friction and wear caused by insufficient lubrication of human joints are important causes of joint inflammation. Pathologically, the main factor in the progression of osteoarthritis is the loss of effective lubrication of the joints. Clinically, hyaluronic acid (HA) is used as a first-line drug to maintain joint lubrication and slow down cartilage damage, based on its safety and effectiveness, simple operation and lack of effective alternative therapies. However, due to the effects of reactive oxygen and free radicals produced by inflammation in some arthritis, hyaluronic acid degrades rapidly in the body and requires frequent injections to achieve good results. Repeated and frequent injections increase the chance of bacterial infection and patient pain. Therefore, studying a joint lubricant that has a lubricating effect and improves inflammation treatment is of great significance for the treatment and improvement of joint inflammation or quality of life. Summary of the invention
[0003] The present application is provided to solve the above defects in the prior art. A multifunctional joint lubricating material and its preparation method and application are needed, providing a joint lubricating material with anti-friction and anti-wear properties, and also having photothermal conversion properties and inflammation treatment properties through loading materials.
[0004] In a first aspect of the present application, a multifunctional joint lubricating material is provided, which includes a base lubricant, and the base lubricant includes a covalent organic framework material (COF) and a poly(ethylene glycol)-poly(N-isopropylacrylamide) (PNIPAm-PEG) microgel layer loaded on the covalent organic framework material, the microgel layer is loaded on the surface and pores of the covalent organic framework material, and the poly(ethylene glycol) and poly(N-isopropylacrylamide) in the microgel layer are grafted and connected by CO covalent bonds.
[0005] In a second aspect of the present application, a method for preparing a multifunctional joint lubricating material as described in any embodiment of the present application is provided, the preparation method comprising: mixing a covalent organic framework material with N-isopropylacrylamide, poly(ethylene glycol) methyl methacrylate, N,N'-methylenebisacrylamide and azobisisobutyramidine hydrochloride in water to obtain a solution containing a lubricant, and subjecting the solution containing the lubricant to solid-liquid separation and drying to obtain a lubricant, and degassing with an inert gas during the reaction.
[0006] The third aspect of the present application provides a use of the joint lubricating material described in any embodiment of the present application in the preparation of a joint lubricating drug or a drug carrier.
[0007] In a fourth aspect of the present application, a medicine is provided, wherein the medicine comprises the joint lubricating material described in any embodiment of the present application.
[0008] The embodiments of the present application provide a multifunctional joint lubricating material, a preparation method and an application thereof, wherein the joint lubricating material comprises a covalent organic framework material and a poly(ethylene glycol)-poly(N-isopropylacrylamide) microgel layer loaded on the covalent organic framework material; the solubility of the covalent organic framework material in an aqueous solution can be improved, the anti-wear and friction-reducing properties can be improved, the wear of the joints can be reduced and the life of the joints can be extended; the covalent organic framework material can be loaded with quantum dots, can be used as an artificial nanozyme to remove ROS, and can also be used for photothermal conversion, thereby assisting in improving the effect of inflammatory treatment; the covalent organic framework material has a porous structure and can be loaded with anti-inflammatory drugs, thereby achieving inflammatory treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] In the drawings, which are not necessarily drawn to scale, the same reference numerals may describe similar parts in different views. The same reference numerals with letter suffixes or different letter suffixes may represent different instances of similar parts. The accompanying drawings generally illustrate various embodiments by way of example and not limitation, and together with the specification and claims, are used to illustrate the embodiments applied for. When appropriate, the same reference numerals are used throughout the drawings to refer to the same or similar parts. Such embodiments are illustrative and are not intended to be exhaustive or exclusive embodiments of the present apparatus or method.
[0010] Figure 1 A transmission electron microscope image of COF-PNIPAm-PEG-MnO2 according to an embodiment of the present application is shown; Figure 2 The dispersibility effect diagram of COF and COF-PNIPAm-PEG-MnO2 according to the embodiments of the present application is shown; Figure 3 A photothermal data diagram of COF-PNIPAm-PEG-MnO2 and ultrapure water according to an embodiment of the present application is shown; Figure 4 Zeta potential data of COF, COF-PNIPAm-PEG, and COF-PNIPAm-PEG-MnO2 according to the examples of the present application are shown; Figure 5 The infrared spectra of COF, COF-PNIPAm-PEG, and COF-PNIPAm-PEG-MnO2 according to the embodiments of the present application are shown; Figure 6 A graph showing the biological toxicity study of COF and COF-PNIPAm-PEG-MnO2 on cells according to the embodiments of the present application is shown; Figure 7 The reciprocating friction curves of H2O and COF-PNIPAm-PEG-MnO2 under the conditions of a load of 1 N and a frequency of 1 Hz according to an embodiment of the present application are shown; Figure 8 The average friction coefficient of COF-PNIPAm-PEG-MnO2 with different concentrations under the conditions of 1 Hz and 5 N according to the embodiments of the present application is shown; Fig. 9 The spectra before and after loading drugs according to the embodiments of the present application are shown, (a) is the infrared spectrum of DS loading; (b) is the infrared spectrum of CLX loading; Fig.10 Data graphs showing the protective effect on inflammation-induced chondrocyte degeneration according to the embodiments of the present application, (a) is a graph showing the expression of Col2α; (b) is a graph showing the expression of TAC1. DETAILED DESCRIPTION
[0011] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is described in detail below in conjunction with the accompanying drawings and specific implementation examples. The embodiments of the present application are further described in detail below in conjunction with the accompanying drawings and specific implementation examples, but are not intended to limit the present application.
[0012] The words "first", "second" and similar words used in this application do not indicate any order, quantity or importance, but are only used to distinguish. The words "include" or "comprise" and similar words mean that the elements before the word include the elements listed after the word, and do not exclude the possibility of including other elements.
[0013] According to an embodiment of the present application, a multifunctional joint lubricating material is provided, which includes a base lubricant, and the base lubricant includes a covalent organic framework material (COF) and a poly(ethylene glycol)-poly(N-isopropylacrylamide) (PNIPAm-PEG) microgel layer loaded on the covalent organic framework material, the microgel layer is loaded on the surface and pores of the covalent organic framework material, and the poly(ethylene glycol) and poly(N-isopropylacrylamide) in the microgel layer are grafted and connected by CO covalent bonds.
[0014] NIPAm and PEGMA as additives can improve the solubility of COF in aqueous solution, making it anti-wear and friction-reducing, which is beneficial to reduce the friction and wear of cartilage in joints and prolong the life of joints.
[0015] In some embodiments, the joint lubricating material further comprises manganese dioxide quantum dots, and the manganese dioxide quantum dots are loaded on the microgel layer. In some embodiments, the manganese dioxide quantum dots comprise manganese dioxide loaded with bovine serum albumin. The manganese dioxide quantum dots can be used as artificial nanozymes to remove ROS and decompose into Mn 2+ After that, it can be quickly excreted from the body through the kidneys, which is non-toxic to the human body for a long time and reduces the impact of reactive oxygen produced by inflammation in arthritis. Loading manganese dioxide quantum dots makes the joint lubricating material have near-infrared light responsiveness, which can responsively release drugs under near-infrared light irradiation to achieve drug delivery. It also has photothermal conversion performance, which helps to improve the effect of inflammation treatment.
[0016] In some embodiments, the joint lubricating material is spherical and has a diameter of 180-200 nm.
[0017] In some embodiments, the joint lubricating material further comprises an anti-inflammatory active ingredient loaded on the covalent organic framework material, and the anti-inflammatory active ingredient is adsorbed onto the covalent organic framework material through hydrogen bonding and / or conjugation.
[0018] The multifunctional joint lubricating material not only has excellent properties of reducing active oxygen, reducing friction and anti-wear, and photothermal conversion, but can also load arthritis treatment drugs through adsorption. Compared with pure water, the addition of this lubricating additive reduces the friction coefficient by 83.9%, and has good biocompatibility and inflammation treatment effects.
[0019] According to an embodiment of the present application, there is also provided a method for preparing a multifunctional joint lubricating material as described in any embodiment of the present application, the preparation method comprising: mixing a covalent organic framework material with N-isopropylacrylamide, poly(ethylene glycol) methyl methacrylate, N,N'-methylenebisacrylamide and azobisisobutylamidine hydrochloride in water to obtain a solution containing a basic lubricant, wherein the basic lubricant comprises a covalent organic framework material and a poly(ethylene glycol)-poly(N-isopropylacrylamide) microgel layer loaded on the covalent organic framework material; and subjecting the solution containing the basic lubricant to solid-liquid separation and drying to obtain the basic lubricant.
[0020] N-isopropylacrylamide and poly(ethylene glycol) methyl methacrylate fully contact the covalent organic framework material, fill the gaps in the covalent organic framework material, and then undergo in-situ polymerization to obtain a basic lubricant.
[0021] In some embodiments, the reaction temperature is 60-80° C., and the reaction time is 1.5-4 h. The reaction time can be 2-3 h, or 3-3.5 h, etc.
[0022] In some embodiments, the mass ratio of the covalent organic framework material to N-isopropylacrylamide, poly(ethylene glycol) methyl methacrylate, N,N'-methylenebisacrylamide and azobisisobutyramidine hydrochloride is: 0.1-5 mg:110-115 mg:0.04-0.05 mL:3-4 mg:0.9-1.2 mg.
[0023] In some embodiments, during the reaction process, degassing is first performed with an inert gas, and then azobisisobutylamidine hydrochloride is added to react; the inert gas may be argon or the like.
[0024] In some embodiments, the solution containing the base lubricant and manganese dioxide quantum dots are mixed and reacted at room temperature to obtain a solution containing a lubricant loaded with manganese dioxide quantum dots, and the solution containing the lubricant loaded with manganese dioxide quantum dots is subjected to solid-liquid separation and drying to obtain a lubricant loaded with manganese dioxide quantum dots.
[0025] In some embodiments, the mass ratio of the covalent organic framework material to the manganese dioxide quantum dots in the base lubricant is 0.5-20:0.02. In some embodiments, the reaction time at room temperature is 20-30 h.
[0026] In some embodiments, the solution of the lubricant containing the loaded manganese dioxide quantum dots is mixed with the anti-inflammatory active ingredient, and the reaction is carried out in the dark to obtain a lubricant solution containing the loaded anti-inflammatory active ingredient and manganese dioxide quantum dots, and the lubricant solution containing the loaded anti-inflammatory active ingredient and manganese dioxide quantum dots is centrifuged and freeze-dried to obtain a lubricant containing the loaded anti-inflammatory active ingredient and manganese dioxide quantum dots. The anti-inflammatory drug is adsorbed onto the COF through hydrogen bonding and conjugation, avoiding the influence of covalent bonds on the activity of drug molecules, and this adsorption method can achieve slow release of the drug, which is conducive to maintaining a good therapeutic effect for a long time, and solves the problem of slow drug absorption and being unfavorable for anti-inflammatory treatment.
[0027] In some embodiments, the mass ratio of the covalent organic framework material to the anti-inflammatory active ingredient in the base lubricant is 0.5-20:4.
[0028] In some embodiments, the anti-inflammatory active ingredients include diclofenac sodium, celecoxib and other ingredients that have anti-inflammatory effects to better treat joint inflammation.
[0029] In some embodiments, the reaction time is 20-30 h in the dark.
[0030] In some embodiments, a method for preparing a covalent organic framework material is also included, and the method for preparing a covalent organic framework material includes: two organic monomers react at room temperature and under the action of a glacial acetic acid catalyst to obtain a covalent organic framework material. In some embodiments, the two organic monomers include 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione and tris(4-aminophenyl)amine.
[0031] In some embodiments, the reaction time at room temperature is 20-30 h. In some embodiments, the mixed solution after the reaction is centrifuged, and the supernatant is removed to obtain a precipitate, and the precipitate is washed with tetrahydrofuran to obtain a covalent organic framework material. In some embodiments, two organic monomers are dissolved in organic solvents respectively and then reacted.
[0032] In some embodiments, the mass volume ratio of 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione, chloroform, tris(4-aminophenyl)amine, methanol, and glacial acetic acid is: 2.5-3.5 mg:1.5-2.5 mg:1 ml.
[0033] In some embodiments, the mass volume ratio of 3,6-bis(5-formylthiophen-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione and chloroform is 9 mg:9-11 ml.
[0034] In some embodiments, the mass volume ratio of tris(4-aminophenyl)amine to methanol is: 1 mg: 3-4 ml.
[0035] According to the embodiments of the present application, there is also provided a use of the joint lubricating material described in any embodiment of the present application in the preparation of a joint lubricating drug or a drug carrier.
[0036] According to an embodiment of the present application, a medicine is also provided, the medicine comprising the joint lubricating material described in any embodiment of the present application. The medicine may also include at least one non-pharmaceutical active ingredient. According to the usual method, the medicine may be prepared into a dosage form in the form of an oral agent, an external agent, a suppository, and a sterile injection solution such as a powder, a granule, a tablet, a capsule, a suspension, an emulsion, a syrup, and a spray.
[0037] The preparation method of the covalent organic framework material involved in the following embodiments: 3,6-bis(5-formylthiophene-2-yl)-2,5-bis(2-ethylhexyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione monomer was added to a beaker, and then chloroform was added to dissolve it to obtain a red-purple solution A; tri(4-aminophenyl)amine monomer was added to a beaker and dissolved with methanol to obtain a light brown solution B; solution A and solution B were mixed, stirred and then glacial acetic acid was added dropwise as a catalyst, and the reaction was carried out at room temperature for 24 hours; after 24 hours, the supernatant was removed by centrifugation to obtain a blue-green precipitate, the precipitate was washed with tetrahydrofuran, and centrifuged until the supernatant became colorless; the product COF was obtained.
[0038] The preparation method of manganese dioxide quantum dots (MnO2-QDs) involved in the following embodiments: Bovine serum albumin was dissolved in deionized water, potassium permanganate was added and stirred until the solution turned into a brown-yellow solution. The solution was then placed in a dialysis bag and dialyzed for 3 days, and finally centrifuged and washed, and vacuum dried to obtain BSA-MnO2, which was recorded as MnO2-QDs.
[0039] Example 1 (1) Modification of covalent organic framework materials: Ultrasonic dispersion of 20 mg of the above product COF in 10 mL of ultrapure water, add 452.8 mg of NIPAm, heat to 35 °C, ultrasonically disperse evenly, then add 0.168 mL of PEGMA and 15.4 mg of MBA and ultrasonically stir for 30 min. Heat to 70 °C, degas with Ar for 40 min, add 4.32 mg of V50, stir for 3 h, centrifuge and remove the supernatant to obtain COF-PNIPAm-PEG base lubricant, then add water to obtain a COF-PNIPAm-PEG solution with a concentration of 20 mg / mL and a volume of 1 mL.
[0040] (2) Loading manganese dioxide quantum dots: Add 0.02 mgMnO2-QDs to the COF-PNIPAm-PEG solution in (1) in batches and stir together for 24 h to obtain a COF-PNIPAm-PEG-MnO2 solution.
[0041] (3) The COF-PNIPAm-PEG-MnO2 solution of (2) was mixed with 4 mg of diclofenac sodium, stirred in the dark for 24 h, centrifuged at 9000 rpm for 10 min, the supernatant was removed, and a small amount of precipitate was transferred to a beaker for freeze-drying to obtain a lubricant loaded with anti-inflammatory active ingredients.
[0042] Example 2 (1) Modification of covalent organic framework materials: Ultrasonic dispersion of 15 mg of the above product COF in 10 mL of ultrapure water, add 452.8 mg of NIPAm, heat to 35 °C, ultrasonically disperse evenly, then add 0.168 mL of PEGMA and 15.4 mg of MBA and ultrasonically stir for 30 min. Heat to 70 °C, degas with Ar for 40 min, add 4.32 mg of V50, stir for 3 h, centrifuge and remove the supernatant to obtain COF-PNIPAm-PEG base lubricant, then add water to obtain a COF-PNIPAm-PEG solution with a concentration of 15 mg / mL and a volume of 1 mL.
[0043] (2) Loading manganese dioxide quantum dots: Add 0.02 mgMnO2-QDs to the COF-PNIPAm-PEG solution in (1) in batches and stir together for 24 h to obtain a COF-PNIPAm-PEG-MnO2 solution.
[0044] (3) The COF-PNIPAm-PEG-MnO2 solution of (2) was mixed with 4 mg of diclofenac sodium, stirred in the dark for 24 h, centrifuged at 9000 rpm for 10 min, the supernatant was removed, and a small amount of precipitate was transferred to a beaker for freeze-drying to obtain a lubricant loaded with anti-inflammatory active ingredients.
[0045] Example 3 (1) Modification of covalent organic framework materials: Ultrasonic dispersion of 10 mg of the above product COF in 10 mL of ultrapure water, add 452.8 mg of NIPAm, heat to 35 °C, ultrasonically disperse evenly, then add 0.168 mL of PEGMA and 15.4 mg of MBA and ultrasonically stir for 30 min. Heat to 70 °C, degas with Ar for 40 min, add 4.32 mg of V50, stir for 3 h, centrifuge and remove the supernatant to obtain COF-PNIPAm-PEG base lubricant, then add water to obtain a COF-PNIPAm-PEG solution with a concentration of 10 mg / mL and a volume of 1 mL.
[0046] (2) Loading manganese dioxide quantum dots: Add 0.02 mgMnO2-QDs to the COF-PNIPAm-PEG solution in (1) in batches and stir together for 24 h to obtain a COF-PNIPAm-PEG-MnO2 solution.
[0047] (3) The COF-PNIPAm-PEG-MnO2 solution of (2) was mixed with 4 mg of diclofenac sodium, stirred in the dark for 24 h, centrifuged at 9000 rpm for 10 min, the supernatant was removed, and a small amount of precipitate was transferred to a beaker for freeze-drying to obtain a lubricant loaded with anti-inflammatory active ingredients.
[0048] Example 4 (1) Modification of covalent organic framework materials: Ultrasonic dispersion of 5 mg of the above product COF in 10 mL of ultrapure water, add 452.8 mg of NIPAm, heat to 35 °C, ultrasonically disperse evenly, then add 0.168 mL of PEGMA and 15.4 mg of MBA and ultrasonically stir for 30 min. Heat to 70 °C, degas with Ar for 40 min, add 4.32 mg of V50, stir for 3 h, centrifuge and remove the supernatant to obtain COF-PNIPAm-PEG base lubricant, then add water to obtain a COF-PNIPAm-PEG solution with a concentration of 5 mg / mL and a volume of 1 mL.
[0049] (2) Loading manganese dioxide quantum dots: Add 0.02 mgMnO2-QDs to the COF-PNIPAm-PEG solution in (1) in batches and stir together for 24 h to obtain a COF-PNIPAm-PEG-MnO2 solution.
[0050] (3) The COF-PNIPAm-PEG-MnO2 solution of (2) was mixed with 4 mg of diclofenac sodium, stirred in the dark for 24 h, centrifuged at 9000 rpm for 10 min, the supernatant was removed, and a small amount of precipitate was transferred to a beaker for freeze-drying to obtain a lubricant loaded with anti-inflammatory active ingredients.
[0051] Example 5 (1) Modification of covalent organic framework materials: Ultrasonic dispersion of 2.5 mg of the above product COF in 10 mL of ultrapure water, add 452.8 mg of NIPAm, heat to 35 °C, ultrasonically disperse evenly, then add 0.168 mL of PEGMA and 15.4 mg of MBA and ultrasonically stir for 30 min. Heat to 70 °C, degas with Ar for 40 min, add 4.32 mg of V50, stir for 3 h, centrifuge and remove the supernatant to obtain COF-PNIPAm-PEG base lubricant, then add water to obtain a COF-PNIPAm-PEG solution with a concentration of 2.5 mg / mL and a volume of 1 mL.
[0052] (2) Loading manganese dioxide quantum dots: Add 0.02 mgMnO2-QDs to the COF-PNIPAm-PEG solution in (1) in batches and stir together for 24 h to obtain a COF-PNIPAm-PEG-MnO2 solution.
[0053] (3) The COF-PNIPAm-PEG-MnO2 solution of (2) was mixed with 4 mg of diclofenac sodium, stirred in the dark for 24 h, centrifuged at 9000 rpm for 10 min, the supernatant was removed, and a small amount of precipitate was transferred to a beaker for freeze-drying to obtain a lubricant loaded with anti-inflammatory active ingredients.
[0054] Example 6 (1) Modification of covalent organic framework materials: Ultrasonic dispersion of 1 mg of the above product COF in 10 mL of ultrapure water, add 452.8 mg of NIPAm, heat to 35 °C, ultrasonically disperse evenly, then add 0.168 mL of PEGMA and 15.4 mg of MBA and ultrasonically stir for 30 min. Heat to 70 °C, degas with Ar for 40 min, add 4.32 mg of V50, stir for 3 h, centrifuge and remove the supernatant to obtain COF-PNIPAm-PEG base lubricant, then add water to obtain a COF-PNIPAm-PEG solution with a concentration of 1 mg / mL and a volume of 1 mL.
[0055] (2) Loading manganese dioxide quantum dots: Add 0.02 mgMnO2-QDs to the COF-PNIPAm-PEG solution in (1) in batches and stir together for 24 h to obtain a COF-PNIPAm-PEG-MnO2 solution.
[0056] (3) The COF-PNIPAm-PEG-MnO2 solution of (2) was mixed with 4 mg of diclofenac sodium, stirred in the dark for 24 h, centrifuged at 9000 rpm for 10 min, the supernatant was removed, and a small amount of precipitate was transferred to a beaker for freeze-drying to obtain a lubricant loaded with anti-inflammatory active ingredients.
[0057] Example 7 (1) Modification of covalent organic framework materials: Ultrasonic dispersion of the above 0.5 mg product COF in 10 mL ultrapure water, add 452.8 mg NIPAm, heat to 35 °C, ultrasonically disperse evenly, then add 0.168 mL PEGMA and 15.4 mg MBA and ultrasonically stir for 30 min. Heat to 70 °C, degas with Ar for 40 min, add 4.32 mg V50, stir for 3 h, centrifuge and remove the supernatant to obtain COF-PNIPAm-PEG base lubricant, then add water to obtain a COF-PNIPAm-PEG solution with a concentration of 0.5 mg / mL and a volume of 1 mL.
[0058] (2) Loading manganese dioxide quantum dots: Add 0.02 mgMnO2-QDs to the COF-PNIPAm-PEG solution in (1) in batches and stir together for 24 h to obtain a COF-PNIPAm-PEG-MnO2 solution.
[0059] (3) The COF-PNIPAm-PEG-MnO2 solution of (2) was mixed with 4 mg of celecoxib, stirred in the dark for 24 h, centrifuged at 9000 rpm for 10 min, the supernatant was removed, and a small amount of precipitate was transferred to a beaker for freeze-drying to obtain a lubricant loaded with anti-inflammatory active ingredients.
[0060] The COF-PNIPAm-PEG-MnO2 prepared in Example 6 was subjected to transmission electron microscopy scanning. Figure 1 As shown, it can be seen that the lubricant is spherical and its particle size is 180-200 nm.
[0061] The dispersibility effect of COF-PNIPAm-PEG-MnO2 prepared in Example 6 was tested. The left side is COF-PNIPAm-PEG-MnO2, and the right side is COF. Figure 2 It can be seen that after adding the additive, the dispersibility of the solution is significantly improved and maintained for a longer time.
[0062] The photothermal data of COF-PNIPAm-PEG-MnO2 prepared in Example 6 under near-infrared light are as follows: Figure 3 The experiment proved that COF-PNIPAm-PEG-MnO2 can quickly heat up to 70 ℃ at a concentration of 1.0 mg / mL, while the temperature of ultrapure water hardly changes under the same conditions. Therefore, COF-PNIPAm-PEG-MnO2 has good photothermal performance.
[0063] The Zeta potential data of COF and COF-PNIPAm-PEG-MnO2 prepared in Example 6 are as follows Figure 4As shown, it is shown that the present application realizes the loading of PNIPAm-PEG-MnO2 on COF, so that the dispersibility of COF in aqueous solution is improved.
[0064] The infrared spectra of COF, COF-PNIPAm-PEG prepared in Example 6 and COF-PNIPAm-PEG-MnO2 prepared in Example 6 are shown in FIG. Figure 5 COF at 2927 cm -1 and 1604 cm -1 There are characteristic peaks at 1109 cm -1 There are characteristic peaks at 525 cm -1 The characteristic peaks of the additive and the carrier were detected on the infrared curve of COF-PNIPAm-PEG-MnO2, which confirmed that the additive was successfully loaded.
[0065] The biological toxicity study of COF and COF-PNIPAm-PEG-MnO2 prepared in Example 6 on cells is shown in the figure Figure 6 The COF and COF-PNIPAm-PEG-MnO2 samples with different concentrations were cultured with cells. The experiment showed that the cell survival rate of COF-PNIPAm-PEG-MnO2 samples with different concentrations (solvent is water) was more than 90%. Therefore, it has good biocompatibility as a synovial fluid additive.
[0066] Zirconia balls and zirconia plates were used as friction pairs, and their tribological properties as joint synovial fluid additives were evaluated using a CFT-I material surface performance comprehensive tester. The reciprocating friction curve of H2O and COF-PNIPAm-PEG-MnO2 prepared in Example 6 under load of 1 N and frequency of 1 Hz is shown in the figure below: Figure 7 The friction coefficient of pure water is about 0.55, and the friction coefficient of COF-PNIPAm-PEG-MnO2 is about 0.085. It can maintain a low friction coefficient for a long time, showing good lubrication performance. Figure 8 In this study, the effects of different concentrations of COF-PNIPAm-PEG-MnO2 (0.5, 1.0, 2.5, 5, 10, 15, 20 mg / mL, solvent: water) on the friction coefficient were studied under the same friction conditions (1 N, 1 Hz). Figure 8The results show that COF-PNIPAm-PEG-MnO2 can achieve better lubrication and friction reduction effects at a concentration of 1 mg / mL. The changes in the friction coefficient of 1 mg / mL COF-PNIPAm-PEG-MnO2 under loads of 1, 3, and 5 N at a frequency of 1 Hz were studied. The lubrication performance of COF-PNIPAm-PEG-MnO2 was tested in detail by changing the load. The results show that under different loads, the friction coefficient of COF-PNIPAm-PEG-MnO2 is much lower than that of pure water, and both show good friction reduction and anti-wear effects.
[0067] The UV spectra of DS (diclofenac sodium) and COF-PNIPAm-PEG-MnO2 loaded with DS prepared in Example 6 are shown in FIG. Fig. 9 As shown in (a), the data show that COF-PNIPAm-PEG-MnO2 has a -1 2927 cm -1 Characteristic peak, DS at 1450cm -1 and 1573 cm -1 These characteristic peaks were detected on the infrared curve of COF-PNIPAm-PEG-MnO2+DS, thus proving the successful loading of DS.
[0068] The UV spectra of CLX (celecoxib) and COF-PNIPAm-PEG-MnO2 loaded with CLX prepared in Example 7 are shown in FIG. Fig. 9 As shown in (ii), CLX at 1390 cm -1 and 1635 cm -1 There are characteristic peaks at the bottom, and the characteristic peaks of the drug and the carrier are detected on the UV curve of COF-PNIPAm-PEG-MnO2+CLX, confirming that the drug is successfully loaded.
[0069] H2O2 was used to establish an oxidative stress environment that induced OA (osteoarthritis) and quantitative real-time polymerase chain reaction (qRT-PCR) analysis was used to track the expression levels of different mRNAs to test the protective effect of the DS-loaded COF-PNIPAm-PEG-MnO2 lubricant prepared in Example 6 on degradation and inflammation inhibition under NIR irradiation; a control group (control, adding PBS), a blank group (blank), a CPP group (COF-PNIPAm-PEG without manganese dioxide loading), a CPP+MnO2+DS+NIR group (COF-PNIPAm-PEG+MnO2+DS+near infrared light), and a DS group were also set up. Test data are shown in Figure 2. Fig.10As shown in (a) and (b), it was found that the lubricating material had an effective protective effect on cartilage under oxidative stress by upregulating Col2α and reducing TAC1 gene, thereby avoiding chondrocyte degradation.
[0070] In summary, it is shown that the multifunctional joint lubricating material with anti-inflammatory activity has practical application value in joint lubrication and arthritis treatment.
[0071] In addition, although exemplary embodiments have been described herein, the scope includes any and all embodiments based on the present application with equivalent elements, modifications, omissions, combinations (e.g., various embodiments intersecting schemes), adaptations or changes. The elements in the claims are to be interpreted broadly based on the language adopted in the claims, and are not limited to the examples described in this specification or during the practice of this application, and the examples are to be interpreted as non-exclusive. Therefore, this specification and examples are intended to be considered as examples only, and the true scope and spirit are indicated by the following claims and the full scope of their equivalents.
[0072] The above description is intended to be illustrative rather than restrictive. For example, the above examples (or one or more schemes thereof) may be used in combination with each other. For example, a person of ordinary skill in the art may use other embodiments when reading the above description. In addition, in the above-mentioned specific embodiments, various features may be grouped together to simplify the present application. This should not be interpreted as an intention that a feature of an application that does not require protection is necessary for any claim. On the contrary, the subject matter of the present application may be less than all the features of an embodiment of a particular application. Thus, the following claims are incorporated herein in the specific embodiments as examples or embodiments, wherein each claim is independently a separate embodiment, and it is considered that these embodiments may be combined with each other in various combinations or arrangements. The scope of the present invention should be determined with reference to the appended claims and the full scope of equivalent forms granted by these claims.
[0073] The above embodiments are only exemplary embodiments of the present application and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present application, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.
Claims
1. A multifunctional joint lubricating material, characterized in that: The joint lubricating material comprises a basic lubricant, which comprises a covalent organic framework material and a poly(ethylene glycol)-poly(N-isopropylacrylamide) microgel layer loaded on the covalent organic framework material. The microgel layer is loaded on the surface and pores of the covalent organic framework material, and the poly(ethylene glycol) and poly(N-isopropylacrylamide) in the microgel layer are grafted and connected through CO covalent bonds.
2. The joint lubricating material according to claim 1, characterized in that: The joint lubricating material further comprises manganese dioxide quantum dots, and the manganese dioxide quantum dots are loaded on the microgel layer.
3. The joint lubricating material according to claim 2, characterized in that: The joint lubricating material is spherical and has a diameter of 180-200 nm.
4. The joint lubricating material according to claim 1, characterized in that: The joint lubricating material further comprises an anti-inflammatory active component loaded on the covalent organic framework material, and the anti-inflammatory active component is adsorbed on the covalent organic framework material through hydrogen bonding and / or conjugation.
5. The method for preparing the joint lubricating material according to claim 1, characterized in that: The preparation method comprises: a covalent organic framework material is mixed with N-isopropylacrylamide, poly(ethylene glycol) methyl methacrylate, N,N'-methylenebisacrylamide and azobisisobutylamidine hydrochloride in water to obtain a solution containing a basic lubricant; the solution containing the lubricant is subjected to solid-liquid separation and drying to obtain a lubricant; and an inert gas is used for degassing during the reaction.
6. The preparation method according to claim 5, characterized in that: The reaction temperature is 60-80°C; the reaction time is 1.5-4 h.
7. The preparation method according to claim 5, characterized in that: The solution containing the base lubricant and the manganese dioxide quantum dots are mixed and reacted at room temperature to obtain a solution containing a lubricant loaded with manganese dioxide quantum dots. The solution containing the lubricant loaded with manganese dioxide quantum dots is subjected to solid-liquid separation and dried to obtain a lubricant loaded with manganese dioxide quantum dots.
8. The preparation method according to claim 7, characterized in that: The solution of the lubricant containing loaded manganese dioxide quantum dots is mixed with a drug, and reacted in the dark to obtain a lubricant solution containing loaded drugs and manganese dioxide quantum dots. The lubricant solution containing loaded drugs and manganese dioxide quantum dots is centrifuged and freeze-dried to obtain a lubricant containing loaded drugs and manganese dioxide quantum dots.
9. Use of the joint lubricating material according to any one of claims 1 to 4 in the preparation of joint lubricating drugs or drug carriers.
10. A drug, characterized in that The medicine comprises the joint lubricating material according to any one of claims 1 to 4.